Physical activity and the brain myelin content in humans - Kujawa, Mariusz J.; Marcinkowska, Anna B.; Grzywińska, Małgorzata; Waśkow, Monika; Romanowski, Alexander; Szurowska, Edyta; Winklewski, Paweł J.; Szarmach, Arkadiusz (Frontiers in Cellular Neuroscience, 2023)
New imaging sequences and biophysical models allow adopting magnetic resonance imaging (MRI) for in vivo myelin mapping in humans. Understanding myelination and remyelination processes in the brain is fundamental from the perspective of proper design of physical exercise and rehabilitation schemes that aim to slow down demyelination in the aging population and to induce remyelination in patients with neurodegenerative diseases. Therefore, in this review we strive to provide a state-of-the art summary of the existing MRI studies in humans focused on the effects of physical activity on myelination/remyelination. We present and discuss four cross-sectional and four longitudinal studies and one case report. Physical activity and an active lifestyle have a beneficial effect on the myelin content in humans. Myelin expansion can be induced in humans throughout the entire lifespan by intensive aerobic exercise. Additional research is needed to determine (1) what exercise intensity (and cognitive novelty, which is embedded in the exercise scheme) is the most beneficial for patients with neurodegenerative diseases, (2) the relationship between cardiorespiratory fitness and myelination, and (3) how exercise-induced myelination affect cognitive abilities.